The Application of "Sets" of Discrete Mathematics everyday in life - Hermawanti, Ninda Putri; Dona, Elsa (CSRID (Computer Science Research and Its Development Journal), 2018)
Mathematics is related to something that can be calculated or something expressed in terms of quantity (number). There are so many economic variables (concepts) that are quantified, such as the price of goods, the amount of goods demanded and offered, the money supply, the level of profit sharing margin, national income, investment level, and so on. Mathematics does not only play a role in quantifying economic variables, but also explores the relationship between economic variables. The relationship of an economic variable with other economic variables is often expressed in the form of an economic model. Because economic variables can be quantified, these economic models can be expressed in the form of mathematical symbols / models.